Analysis of Quality Improvement of Finishing Work in The Development of Puncak CBD Surabaya Apartment - Damayanti, Safira; Wiguna, I Putu (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2019)
The quality is one of the important factors in the success of construction project. In fact, cost of construction is vain until 6-15% because reworking and process of work is late. Wika Building Contractor have standart of quality, name is QPASS ( Quality Performance Assessment Support System ) for all projects. Puncak CBD Surabaya Apartment,is one of Wika Building Project that having lower quality standart value in 2018. In this study, the six sigma method with the DMAIC (Define, Measure, Analyze, Improve, Control) approach was used to improve low quality values. Starting with identify works with defect largest based on QPASS monthly report, then calculate the dominant defect using a level of sigma. The research results show the wall work having highest total number of defects. The wall work defect with sigma value under 3 level are joint of wall is not perpendicular, cracked plaster seen from 1.5 m distance and flaking paint. At the improve phase, determined the best action plan for handle cause factor of the three such defect. The best action was determined are do thickening and adjust the angle of wall for defect â€œJoint of wall is not perpendicularâ€, giving direction for workers about correct plaster mixture for defect â€œCracked plaster seen from 1.5 m distanceâ€, and cleaning of wall before painting for defect â€œ Flaking paintâ€.